An Analysis of Lexical Cohesion Found in "Red" Song Lyrics - Putirulan, Mauren Mauritsya; Cahya, Rahmat Adi; Latuihamallo, Cindy Itamar (Huele: Journal of Applied Linguistics, Literature and Culture, 2023)
This study examines patterns of lexical cohesion in Taylor Swift's song "RED" through systematic discourse analysis. Following Halliday and Hasan's (1976) framework for lexical cohesion, supplemented by contemporary approaches to discourse analysis, we analyzed how various cohesive devices contribute to the song's narrative structure and emotional impact. Our qualitative analysis identified three primary types of lexical cohesion: repetition (56.3%), antonymy (25%), and synonymy (18.7%). The findings demonstrate sophisticated use of repetition patterns, particularly in emotional expressions using gerund forms, creating parallel structures that emphasize emotional progression. The study identifies a complex system of color-based cohesion, with color terms serving both referential and symbolic functions throughout the narrative. Strategic placement of antonymic pairs creates emotional dimensionality, while the use of near-synonymy allows for nuanced emotional expression. These findings contribute to our understanding of how contemporary songwriters use linguistic devices to create emotional impact and maintain narrative coherence. The research advances both theoretical understanding of lexical cohesion and practical insights into effective songwriting techniques, while suggesting new approaches to analyzing popular music lyrics. The study's limitations, including its focus on a single text, suggest directions for future research examining these patterns across a broader corpus of contemporary songwriting.